The impact of structural social capital on farm income in the Czech Republic - Axel Wolz; Jana Fritzsch; Jitka Pencáková (Agricultural Economics (Zemědělská ekonomika), 2006)
The change of the economic system from the socialist central planning system to the market economy required the reorganisation not only of agricultural production, but also of the organisations supporting it. In the Czech Republic, agricultural production is characterised by a dualistic structure, i.e. private farmers on the one side and corporate farms on the other. However, among both groups some had been economically more successful than others. In general, a varying adoption of production factors, i.e. land, labour and capital is identified as being of influence. Namely, their ability to collaborate with other farms which is discussed under the concept of social capital, will be analysed in this paper. Based on the findings of a survey among a sample of 62 farms by adopting factor and multiple regression analysis, it can be deduced that social capital is indeed a significant factor determining farm income. – – Změna hospodářského systému ze socialistického centrálního plánování na tržní ekonomiku vyžadovala reorganizaci nejen zemědělské výroby, ale i organizací, které ji podporují. V České republice je zemědělská výroba charakterizována dvojí strukturou, tzn. soukromými zemědělci na straně jedné a zemědělskými podniky na straně druhé. Avšak v obou těchto skupinách mají někteří zemědělci větší ekonomické úspěchy než ostatní. Zejména na to má vliv odlišné přijímání výrobních faktorů, tj. půdy, pracovních sil a kapitálu. Schopnost zemědělců spolupracovat s dalšími farmami, která je diskutována v konceptu sociální kapitálu, bude předmětem tohoto článku. Na základě zjištění z průzkumu, který byl proveden na vzorku 62 farem pomocí faktorové analýzy a mnohonásobné regrese, je možné vyvozovat, že sociální kapitál je skutečně důležitým faktorem určujícím výši zisku farmy.
Keywords: 330; corporate farms; private farms; cross sectional models; zemědělské podniky; soukromé farmy; průřezové modely